Central proliferation and neurogenesis is impaired in type 2 diabetes and prediabetes animal models. - Juan Jose Ramos-Rodriguez (Public Library of Science (PLoS), 2014)
Type 2 diabetes (T2D) is an important risk factor to suffer dementia, including Alzheimer's disease (AD), and some neuropathological features observed in dementia could be mediated by T2D metabolic alterations. Since brain atrophy and impaired neurogenesis have been observed both T2D and AD we analyzed central nervous system (CNS) morphological alterations in the db/db mice (leptin receptor KO mice), as a model of long-term insulin resistance and T2D, and in C57Bl6 mice fed with high fat diet (HFD), as a model of diet induced insulin resistance and prediabetes. Db/db mice showed an age-dependent cortical and hippocampal atrophy, whereas in HFD mice cortex and hippocampus were preserved. We also detected increased neurogenesis and cell proliferation rates in young db/db mice when compared with control littermates. Our study shows that metabolic parameters serve as predictors of both atrophy and altered proliferation and neurogenesis in the CNS. Moreover in the cortex, atrophy, cell proliferation and neurogenesis were significantly correlated. Our data suggest that T2D may underline some of the pathological features observed in the dementia process. They also support that blood glucose control in elderly patients could help to slow down dementia evolution and maybe, improve its prognosis.